Knowledge, attitude and practice of community pharmacy personnel in tuberculosis patient detection: a multicentre cross-sectional study in a high-burden tuberculosis setting - Rovina Ruslami; Rizky Abdulah; Rob E Aarnoutse; Ivan Surya Pradipta; Khairunnisa Khairunnisa; Muh Akbar Bahar; Mersa Nurain Kausar; Efi Fitriana (BMJ Open)
Introduction Control of tuberculosis (TB) is hampered by suboptimal case detection and subsequent delays in treatment, which is worsened by the COVID-19 pandemic. The community pharmacy is reported as the place for first aid medication among patients with TB. We, therefore, analysed knowledge, attitude and practice (KAP) on TB patient detection (TBPD) of community pharmacy personnel, aiming to find innovative strategies to engage community pharmacies in TBPD.Methods A multicentre cross-sectional study was performed in four areas of Indonesia’s eastern, central and western parts. Pharmacists and pharmacy technicians who worked in community pharmacies were assessed for their characteristics and KAP related to TBPD. Descriptive analysis was used to assess participant characteristics and their KAP, while multivariable regression analyses were used to analyse factors associated with the KAP on TBPD.Results A total of 1129 participants from 979 pharmacies, comprising pharmacists (56.6%) and pharmacy technicians (43.4%), were included. Most participants knew about TB. However, knowledge related to TB symptoms, populations at risk and medication for TB were still suboptimal. Most participants showed a positive attitude towards TBPD. They believed in their professional role (75.1%), capacity in TB screening (65.4%) and responsibility for TBPD (67.4%). Nevertheless, a lack of TBPD practice was identified in most participants. Several factors significantly associated with performing the TBPD practice (p<0.05), such as TB training experience (p<0.001), provision of a drug consultation service (p<0.001), male gender (p<0.05), a positive attitude towards TBPD (p<0.001), short working hours (p<0.001) and central city location of the pharmacy (p<0.05).Conclusions Most participants had good knowledge and attitude, which did not translate into actual TBPD practice. We identified that TB educational programmes are essential in improving the KAP. A comprehensive assessment is needed to develop effective strategies to engage the community pharmacy in TBPD activities.